Optical measurement of breathing: Algorithm volume calibration and preliminary validation on healthy trained subjects - Massaroni, C.; Cassetta, E.; Levai, I. K.; Winter, S.; Dickinson, J. W.; Silvestri, S. (2016 38th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC), 2016)
The use of optical technologies may be beneficial when measuring breathing biomechanics. The purpose of this study was twofold: i) to enhance the optoelectronic plethysmography (OEP) algorithm performance for the volume estimation by the use of a novel volume calibration procedure and ii) to compare the OEP volumes gained by a commercial optoelectronic system against actual respiratory volumes measured by a breath-by-breath gas analyzer (BbB). The OEP volume algorithm calibration was performed by the use of a novel volume calibration procedure based on both a calibrator device that delivered known volumes changes and one ad-hoc designed software for the static and dynamic calibration analysis. OEP algorithm threshold, accuracy, repeatability and the volume algorithm calibration were investigated. Tidal volume (VT) measurements performed simultaneously by the calibrated OEP algorithm and BbB analyzer were compared. VT measured simultaneously by OEP and BbB was collected during submaximal exercise tests in five trained healthy participants in two conditions (with hunched shoulders and in normal shoulder position). The two methods were compared by linear regression and Bland-Altman analysis in both positions. The average difference between methods and the discrepancy were calculated. The OEP-BbB correlation was high in both positions, R 2 =0.92 and R 2 =0.97 for hunch and normal one, respectively. Bland-Altman analysis demonstrated that OEP algorithm systematic difference was lower than 100mL. The limits of agreement assessed in both positions are comparable. The difference between measurements suggesting that OEP may be a useful tool to analyze chest wall volume changes and breathing mechanics during intense exercise.